Slip characteristics of planar and rough granite fractures under unloading normal force - Tao, Zongheng; Tang, Wei; Li, Xingling; Tao, Kang; Dang, Wengang (Frontiers in Earth Science, 2024)
Unloading processes are common in natural systems. Intense unloading activities can alter the frictional equilibrium of faults and induce their instabilities. Understanding the slip behavior of faults under stress unloading conditions is helpful in guiding engineering practices. We conducted a series of direct shear experiments under linear-unloading normal force conditions considering the influences of initial normal forces, initial shear forces, and normal unloading rates on planar and rough granite fractures. The experimental results showed that planar fracture exhibits sudden slip events during normal unloading, while rough fracture mostly displays stable sliding behavior. The planar fracture demonstrates an exponential increase in sliding distance and velocity at the end of each slip event. The rough fracture usually exhibits a quasi-static stage before rapid slip events. In addition, the accumulative sliding distance at the slip activation moment (at the first moment when sliding velocity is greater than 0.05 mm/s) for the planar fracture decreases with lower normal unloading rate, larger shear force and larger normal force, while its variation trend for rough fracture is opposite. These findings provide valuable insights into fault slip behavior under stress unloading, aiding in mitigating associated risks in engineering applications.